Professional Writing - Kesteven, Lisa. author. aut Link
XIII, 186 p.
Keywords: This book has been designed specifically for students in writing classes and other writers interested in developing proficient writing careers in a professional environment. As professional writing continues to change rapidly alongside digital developments, this book frames professional writing particularly for 'creative' and other writers. The professional world needs writers with a diverse portfolio of skills and capabilities; if writers can master these, they are more able to make a living from their writing and support their more creative endeavours. Each chapter includes a comprehensive range of exercises to build professional skills, along with learning objectives, case studies, worked examples, tips for success, and suggested websites and further reading. Lisa Kesteven is a lecturer on Creative and Professional Writing and has designed and led modules on Professional Writing. As well as being a writer of fiction and non-fiction, Lisa has worked freelance for a number of years and has her own freelancing business. Andrew Melrose is an Emeritus Professor of Critical and Creative writing and a writer. He has over 160 film, fiction, non-fiction, research, songs, poems, chapters and other writing credits, including 15 films and 39 books.